KESESUAIAN LOKASI DAN TANGGAPAN MASYARAKAT UNTUK TEMPAT PEMROSESAN AKHIR (TPA) SAMPAH DI KOTA KOTAMOBAGU - Hariyono ., Gumalangit; Zetly ., Tamod; Bobby ., Polii (AGRI-SOSIOEKONOMI, 2017)
This study aims to analyze the appropriate location and community responses for waste landfill sites and to determine the factors that limit the level of land suitability for waste landfill in Kota Kotamobagu. The study was conducted in the designated area for the development of the Kotamobagu Municipal TPA location based on the RTRW document of Kota Kotamobagu for three months from February to March 2017. This research is observational. Research data is analyzed through quantitative descriptive method. The results showed that in the area designated as the location of TPA development in Kota Kotamobagu there is one candidate location that enter on the category of potential worthy in the area of West Mongkonai Village based on the criteria of the feasibility of SNI 03-3241-1994. Communities around the landfill development / expansion sites for the Small Poyowa TPA tend to accept the presence of waste landfill and for the development site of West Mongkonai waste landfill, people in the area tend to deny the existence of waste landfill sites. The limiting factor of land suitability for the landfill location in Kota Kotamobagu is classified into two namely the main limiting factor that is the social environment of the community in the form of rejection of the landfill location by the community around the landfill site and the physical limiting factor which consists of land permeability, rain intensity and agricultural area.